Diffusion Kurtosis Imaging of Neonatal Spinal Cord in Clinical Routine - Trò, Rosella; Roascio, Monica; Tortora, Domenico; Severino, Mariasavina; Rossi, Andrea; Cohen-Adad, Julien; Fato, Marco Massimo; Arnulfo, Gabriele (Frontiers in Radiology, 2022)
Diffusion Kurtosis Imaging (DKI) has undisputed advantages over more classical diffusion Magnetic Resonance Imaging (dMRI), as witnessed by a fast-increasing number of clinical applications and software packages widely adopted in brain imaging. However, in the neonatal setting, DKI is still largely underutilized in particular in Spinal Cord (SC) imaging because of its inherently demanding technological requirements. Due to its extreme sensitivity to non-gaussian diffusion, DKI proves particularly suitable for detecting complex, subtle, fast microstructural changes occurring in this area at this early and critical stage of development, and not identifiable with only DTI. Given the multiplicity of congenital anomalies of the spinal canal, their crucial effect on later developmental outcome, and the close interconnection between SC region and the above brain, managing to apply such a method to the neonatal cohort becomes of utmost importance. This study will (i) review the mention current methodological challenges associated with application of advanced dMRI methods like DKI in early infancy, (ii) illustrate the first semi-automated pipeline built on Spinal Cord Toolbox (SCT) for handling with DKI data of neonatal SC, from acquisition setting to estimation of diffusion measures, through accurate adjustment of processing algorithms customized for adult SC, and (iii) present results of its application in a pilot clinical case study. With the proposed pipeline, we preliminarily show that DKI is more sensitive than DTI-related measures to alterations caused by brain White Matter Injuries in the underlying cervical SC.